'Flipping' the Classroom. (September 2016) - Billings, Diane M.
Abstract : This article is one in a series on the roles of adjunct clinical faculty and preceptors, who teach nursing students and new graduates to apply knowledge in clinical settings. This article describes the benefits and challenges of using a "flipped" classroom to promote active engagement among learners and more meaningful interaction between learners and educators.